Onychomycosis Due to Fusarium oxysporum in Sulumaniyah City, Iraq - Sazan Jamal Gharib; Samir Khalaf Abdullah (Journal of Clinical and Diagnostic Research, 2020)
Onychomycosis is a fungal infection of the nail plate of fingernails or toenails that is caused by dermatophytes, non-dermatophyte filamentous fungi or yeasts. An opportunistic pathogenic fungus was isolated from toenail of a 38-year-old female with newly diagnosed Acute Myeloid Leukaemia (AML) which appeared to belong to the genus Fusarium. Identification of aetiologic agent was performed by morphological and cultural characteristics and was confirmed by sequencing of the Internal Transcribed Spacer (ITS) region of rDNA. The isolated Fusarium oxysporum in this paper is the first case of its kind to be sequenced and reported by molecular method in Iraq.